Representasi Makna Pantang Menyerah dalam Lirik Lagu Super Junior “Express Mode” - Febriany, Febriany; Putri, Pusparani Sahran; Maulana, Mohammad Iqbal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
Psychological pressure experienced by younger generations due to identity crises and life uncertainty has created a demand for the representation of positive values in popular culture. Express Mode, a song by Super Junior, serves as a medium that conveys the theme of perseverance and resilience. This study aims to analyze how the meaning of never giving up is constructed in the song’s lyrics using Roland Barthes’ semiotic approach. The research method is descriptive qualitative, focusing on three levels of meaning: denotative, connotative, and myth. The findings show that the lyrics construct the image of a modern hero who is progressive and determined in facing challenges. This representation is reinforced by Super Junior’s real-life experience as a group active for over two decades in the entertainment industry. The song functions as a cultural agent that conveys ideological values such as courage, optimism, and determination. In conclusion, Express Mode builds a symbolic narrative that inspires emotional strength among today’s youth.